Primary Hyperoxaluria Diagnosed Based on Bone Marrow Biopsy in Pancytopenic Adult with End Stage Renal Disease - Pardis Nematollahi; Fereshteh Mohammadizadeh (Case Reports in Hematology)
Inborn errors of metabolism cause increase of metabolites in serum and their deposition in various organs including bone marrow. Primary hyperoxaluria (PH) is a rare inborn error in the pathway of glyoxylate metabolism which causes excessive oxalate production. The disease is characterized by widespread deposition of calcium oxalate (oxalosis) in multiple organs. Urinary tract including renal parenchyma is the initial site of deposition followed by extrarenal organs such as bone marrow. This case report introduces a 54-year-old woman with end stage renal disease presenting with debilitating fatigue and pancytopenia. The remarkable point in her past medical history was recurrent episodes of nephrolithiasis, urolithiasis, and urinary tract infection since the age of 5 years and resultant end stage renal disease in adulthood in the absence of appropriate medical evaluation and treatment. She had an unsuccessful renal transplantation with transplant failure. The patient underwent bone marrow biopsy for evaluation of pancytopenia. Microscopic study of bone marrow biopsy led to the diagnosis of primary hyperoxaluria.